2022
DOI: 10.3390/pr10030615
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Extraction Process of Anthocyanins from Jussara (Euterpe edulis) Using Deep Eutectic Solvents

Abstract: New strategies for obtaining target bioactive compounds and natural pigments with the use of “green solvents” are consistently being developed, and deep eutectic solvents are (DES) a great alternative. This work established the significant variables and models for anthocyanin extraction, using DES and experimental design, of Euterpe edulis Mart. (jussara) fruit pulp, an endangered palm tree from the Brazilian Atlantic Forest. From a screening of seven initially tested DES, choline chloride/xylitol-based solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The most plausible justification remains on the possible formation of supramolecular aggregates between the eutectic solvent and the positively charged anthocyanins, acting as a physical shield and protecting the colorants from their interaction with the oxidative stressors. 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most plausible justification remains on the possible formation of supramolecular aggregates between the eutectic solvent and the positively charged anthocyanins, acting as a physical shield and protecting the colorants from their interaction with the oxidative stressors. 14…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some authors reported that when eutectic solvents formed with cholinium chloride : xylitol are applied to extract anthocyanins from Euterpe edulis fruits, there was an increase in the shelf-life of the colorants compared to those extracted with methanol. 14 Other examples have also been investigated, including combining eutectic solvents with high-pressure systems, such as those reported by Benvenutti and co-workers. 15 However, some gaps remain, especially regarding the thermal stability and purity of the colored extracts obtained by combining a high-pressure technology with alternative solvents.…”
Section: Introductionmentioning
confidence: 99%
“…However, some challenges are related to the application of anthocyanins as a food ingredient due to their instability through the process involving high temperatures or even changes in pH (Braga, Murador, et al, 2018; Vannuchi et al, 2022). In this sense, several techniques have been studied to improve the stability of bioactive compounds, including the freeze‐drying process (Braga, Rocha, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The half-life is a very important parameter in this evaluation, because it reflects the time required to halve the concentration of the compound and, in this study, we observed that ChCl:AA obtained the longest half-life, regardless of the temperature tested, thus it has greater ability to stabilize hesperidin and narirutin compared to conventional solvents (ethanol/water 50%, v/v; and water). The ability of eutectic mixtures to stabilize phenolic compounds can be explained by their intermolecular interactions, mainly due to hydrogen bonds, where this interaction reduces oxidative degradation because it decreases the movement of solute molecules and consequently reduces the contact with oxygen at the DES and air interface, as reported by (Barbieri et al 2020;Vannuchi et al, 2022). These interactions reduce the mobility of solutes, decreasing their contact with oxygen and water, consequently reducing their oxidative and hydrolytic degradation.…”
mentioning
confidence: 97%